Examining the Need for Social Approval as a Predictor of Attitudes Towards the Teaching Profession - Mehtap Saracoglu; Mustafa Kahyaoğlu (Dinamika Ilmu, 2021)
The aim of the study is to reveal the effect of the need for social approval on the prediction of attitudes towards the teaching profession, which has an important role in teachers’ behaviors in educational settings. In this way, the effect and importance of the need for social approval such as sensitivity to the judgments of others, social retreat, and making a positive impression on others were examined. The research model was carried out according to relational scanning patterns from quantitative research methods. The population of the study has consisted of university students studying at the Faculty of Education in a university located in the Southeastern Anatolia Region, and the sample has consisted of 478 pre-service teachers. The sample of the study was determined according to the non-selective sampling method. The data in the study were obtained by “Attitude scale towards the teaching profession” and “Social approval needs scale”. Independent sample t-test, one-way ANOVA, Pearson Moments Correlation, and linear regression analysis were used to analyze the data. As a result of the research, it was determined that the attitudes of pre-service teachers towards the teaching profession were “high” and social approval needs were “moderate”. In the study, it was determined that the variables of the teachers’ sensitivity to the judgments of others, social retreat, and leaving a positive impression on others had a significant relationship with the attitude of the pre-service teachers towards the teaching profession. These variables explain 10% of the total variance in pre-service teachers’ attitudes towards the teaching profession. It has been determined that the variables of sensitivity to the judgments of others and leaving a positive impression on others are significant predictors of attitudes towards the teaching profession, while the social retreat variable does not predict significantly.